Particle-Associated Microbial Community in a Subtropical Lake During Thermal Mixing and Phytoplankton Succession - Schweitzer-Natan, Orna; Ofek-Lalzar, Maya; Sher, Daniel; Sukenik, Assaf (Frontiers in Microbiology, 2019)
Ecosystem dynamics in monomictic lakes is characterized by seasonal thermal mixing and stratification. These physical processes bring about seasonal variations in nutrients and organic matter fluxes, affecting the biogeochemical processes that occur in the water column. These dynamics are generally reflected in seasonal structural changes in the phytoplankton and bacterioplankton community. In this study, we analyzed the structure of the particle-associated bacterial community in Lake Kinneret (Sea of Galilee, Israel), using 16S amplicon sequencing and its associations to phytoplankton populations. The study was carried out during late winter and early spring, a highly dynamic period in terms of thermal mixing, nutrient availability, and shifts in phytoplankton composition. Structural changes in the bacterioplankton population corresponded with limnological variations in the lake. In terms of the entire heterotrophic community, the structural patterns of particle-associated bacteria were partly explained by abiotic factors such as pH, ammonia, water temperature and nitrate. However, analysis of microbial taxon-specific interactions with phytoplankton species revealed a strong association between specific bacterial populations and the presence of different phytoplankton species, such as the cyanobacterium Microcystis, as well as the dinoflagellates Peridinium and Peridinopsis. We found that Brevundimonas, a common freshwater genus, and Bdellovibrio, a well-known Gram-negative bacteria predator, were positively associated to Microcystis, suggesting a potentially important role of these three keystone taxa in the microbial ecology of the lake. Our results show that the dynamics of environmental abiotic conditions, rather than the specific phytoplankton assemblages, are the major drivers of changes in community structure as a whole. Nevertheless, some specific bacteria may be linked and interact with specific phytoplankton, which can help us gain further understanding of the role of these interactions in the development of phytoplankton assemblages in the lake.